Quasi-Mental Retarded Represented in Speech Act of Forrest’s Utterances in Forrest Gump Movie. - Feisal Muhammad (LINGUISTICA, 2018)
The study entitled Quasi-Mental Retarded Represented in Speech Act of Forrest’s Utterances in Forrest Gump Movie. The objectives of the study were to find out the types of speech acts found in Forrest’s utterances of Forrest Gump Movie and to describe the function speech acts were used by main character that had a mental retardation. The study was conducted by applying descriptive qualitative design. The data of the study were utterances that used by main character in Forrest Gump movie, and there were 620 utterances found in Forrest’s utterances. Yule’s theory deals with types of speech acts were applied to analyze the data. The findings of the study showed that the types of speech acts were realized in Forrest’s utterances with the ratio; Declaration acts were 24 (3,87%), Representative acts were 443 (71,45%), Expressive acts were 44 (7,11%), Directive acts were 85 (13,70%) and Commissive acts were 24 (3,87%). The representative acts was one of speech acts type that most dominant uttered by Forrest in Forrest Gump Movie. It showed that mental retardation disorder wanted to represent a world as they believe. Keywords:types of speech acts, mental retardation disorder